Tetrabromoepifenchone: a convenient precursor for the synthesis of chiral bicyclo[2.2.1]heptane and bicyclo[2.1.1]hexane derivatives. Issue 15 (31st August 2015) - Ryzhenko, Olga O.; Gorichko, Marian V.
Graphical abstract: Abstract: The regiospecific reduction and Favorskii rearrangement of enantiopure tetrabromoepifenchone, which could be easily obtained by bromination of camphor, have been investigated. The selective formation of new functionalized chiral bicyclo[2.2.1]heptane and bicyclo[2.1.1]hexane derivatives in good yield has been demonstrated. Our approach provides a simple pathway for the large-scale synthesis of a wide range of novel functionalized bicyclic terpenoids starting from easily available camphor. Abstract : (1 S, 4 S, 7 R )-1, 7-Dibromo-4-(bromomethyl)-3, 3-dimethylbicyclo[2.2.1]heptan-2-one: С10 Н13 ОBr3 Ee = 100% [ α ]D 20  = −41.0 ( c 0.5, MeOH) Source of chirality: ( R )-(+)-camphor Abstract : (1 S, 4 R, 7 R, 1′ S, 4′ R, 7′ R )-4, 4′-( E )-Ethene-1, 2-diylbis(1, 7-dibromo-3, 3-dimethylbicyclo[2.2.1]heptan-2-one): С20 Н24 О2 Br4 Ee = 100% [ α ]D 20  = +68.3 ( c 0.95, DMSO) Source of chirality: ( R )-(+)-camphor Abstract : (1 R, 4 R, 1′ R, 4′ R )-4, 4′-( E )-Ethene-1, 2-diylbis(1-bromo-3, 3-dimethylbicyclo[2.2.1]heptan-2-one): С20 Н26 О2 Br2 Ee = 100% [ α ]D 20  = +33.6 ( c 0.654, DMSO) Source of chirality: ( R )-(+)-camphor Abstract : (1 R, 4 R, 6 S )-6-Bromo-4-(dibromomethyl)-5, 5-dimethylbicyclo[2.1.1]hexane-1-carboxylic acid: С10 Н13 О2 Br3 Ee = 100% [ α ]D 20  = −1.2 ( c 0.5, MeOH) Source of chirality: ( R )-(+)-camphor Abstract : (1 R, 4 S, 6 S )-6-Bromo-4-(bromomethyl)-5, 5-dimethylbicyclo[2.1.1]hexane-1-carboxylic acid: С10 Н14 О2 Br2 Ee = 100% [ α ]D 20  = +33.2 ( c 0.5, MeOH) Source of chirality: ( R )-(+)-camphor Abstract : (1 R, 4 S, 6 R ) - 6-Bromo-4, 5, 5-trimethylbicyclo[2.1.1]hexane-1-carboxylic acid: С10 Н15 О2 Br Ee = 100% [ α ]D 20  = −99.8 ( c 0.5, MeOH) Source of chirality: ( R )-(+)-camphor Abstract : (1 R, 4 R )-4, 5, 5-Trimethylbicyclo[2.1.1]hexane-1-carboxylic acid: С10 Н16 О2 Ee = 100% [ α ]D 20  = −7.2 ( c 0.5, MeOH) Source of chirality: ( R )-(+)-camphor Abstract : (1 R, 4 R, 6 R, 1′ R, 4′ R, 6′ R )-4, 4′-( E )-Ethene-1, 2-diylbis(6-bromo-5, 5-dimethylbicyclo[2.1.1]hexane-1-carboxylic acid): С20 Н26 О4 Br2 Ee = 100% [ α ]D 20  = −21.6 ( c 0.95, EtOH) Source of chirality: ( R )-(+)-camphor Abstract : (1 R, 4 R, 1′ R, 4′ R )-4, 4′-( E )-Ethene-1, 2-diylbis(5, 5-dimethylbicyclo[2.1.1]hexane-1-carboxylic acid): С20 Н28 О4 Ee = 100% [ α ]D 20  = +15.0 ( c 0.945, EtOH) Source of chirality: ( R )-(+)-camphor Abstract : (1 S, 4 S, 7 R ) - 4, 7-Dibromo-2, 2-dimethyl-3-oxobicyclo[2.2.1]heptane-1-carboxylic acid: С10 Н12 О3 Br2 Ee = 100% [ α ]D 20  = −11.2 ( c 0.5, MeOH) Source of chirality: ( R )-(+)-camphor Abstract : (1 S, 4 R )-4-Bromo-2, 2-dimethyl-3-oxobicyclo[2.2.1]heptane-1-carboxylic acid: С10 Н12 О3 Br Ee = 100% [ α ]D 20  = −0.4 ( c 0.5, MeOH) Source of chirality: ( R )-(+)-camphor